(3fjd GdYdG aj GdYWa HdGs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3SCdJ CcQec Gddg Yf bGe QLd dRjO, gd jUM gPg GdJQcjH hCf GdTjN CHG MjGf LRe HGeJfGYg s
(3BNQgG (B:s
(3hdjS aj bhdfG eG bGe GdfGS hdG RjO hgPG eG bOQg Gddg YGdi ef cJGHJj LhGHkG ddhdO aGdhdO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3Hg VHWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B106 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B102 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B337 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1994s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs